A research note on the determinants and consequences of outsourcing using German data - John T. Addison; Lutz Bellmann; André Pahnke; Paulino Teixeira (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
Using German data from the Institute for Employment Research Establishment Panel, this paper constructs two main measures of outsourcing and examines their determinants and consequences for employment. There are some commonalities in the correlates of the two measures of outsourcing, as well as agreement on the absence of adverse employment effects across all industries. For one specification, however, some negative effects are reported for manufacturing industry, balanced by positive effects for the services sector for another. But there are no obvious indications of survival bias. This is because the association between outsourcing and plant closings is predominantly negative, albeit poorly determined.
Keywords: F16; J23; 330; outsourcing - Auswirkungen; Beschäftigungseffekte; IAB-Betriebspanel; Wirtschaftszweige; verarbeitendes Gewerbe; Dienstleistungsbereich; Ausland; Niedriglohnland; Betriebsstilllegung; outsourcing - Determinanten; Arbeitskosten; Kostensenkung